RAGAM POLA TABUHAN TAHAR PADA KESENIAN HADRAH DI DESA TUMUK MANGGIS KABUPATEN SAMBAS - Triatmiko, Ilfan (Universitas Tanjungpura, 2024)
This research is motivated by the uniqueness of the various patterns of Tahar wasps which are different from other Tahar wasps. The purpose of this study is to describe the technique of playing and analyzing the various patterns of the tahar wasp. The method used is a descriptive method with a qualitative research form. The approach used is a musicological approach. Sources of data in this study are Rabudin, Yuhendri and Mulyadi. The data of this research are the results of interviews, observations, documentation and notebooks regarding various patterns of tahar wasps and cameras. Checking the validity of the data in this study by triangulation and extension of observations. Data analysis in this study uses three flow of activities, namely data reduction, data presentation, and drawing conclusions. The results of this study are the technique of playing and various patterns of Tahar wasps in hadrah art in Tumuk Manggis Village, Sambas Regency. Tahar musical instruments in this hadrah art have two sound colors, namely